2022
DOI: 10.1051/parasite/2022013
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Theileria spp. and investigation of hematological profiles of their infections in goats in Hainan Island, China

Abstract: Theileria spp. are a group of parasites primarily transmitted by ticks and can pose a significant threat to domestic and wild animals globally. The main objective of this study was to understand the epidemiology of Theileria spp. in goats of Hainan Island/province, which is the only tropical region of China, and to study their hematological profiles in naturally infected goats. A total of 464 blood samples were collected from randomly selected local adult goats (Capra hircus, local domestic breed with black ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Piroplasma and Anaplasma detection rates significantly differed among the location of the goats. The same was observed in goat herds from China [ 29 ], Tunisia [ 40 ], and Oman [ 44 ]. Location-specific factors in this study, such as management practices and macroclimatic conditions that affect tick proliferation, may be attributed to the different sampling sites characterized by diverse topography, terrain, microclimate, and fauna.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Piroplasma and Anaplasma detection rates significantly differed among the location of the goats. The same was observed in goat herds from China [ 29 ], Tunisia [ 40 ], and Oman [ 44 ]. Location-specific factors in this study, such as management practices and macroclimatic conditions that affect tick proliferation, may be attributed to the different sampling sites characterized by diverse topography, terrain, microclimate, and fauna.…”
Section: Discussionsupporting
confidence: 66%
“…Herein, we present the first molecular identification of Babesia, Theileria, and Anaplasma in goats from the Philippines. A high detection rate of piroplasma DNA was recorded in goats (77.02%), which was higher than caprine Babesia and Theileria rates recorded in Pakistan (5–40.80%) [ 25 , 26 ], Turkey (21.40%) [ 27 ], Italy (11.70%) [ 3 ], China (11.90–34.70%) [ 28 , 29 ], Ethiopia (1.90%) [ 30 ], and Tunisia (4.70%) [ 31 ], while comparable to that from Malawi (72.70%) [ 32 ]. The detection rate (38.64%) of Anaplasma spp.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported a prevalence of 5% of T. luwenshuni in the Rayong and Chonburi provinces of Thailand [43]. T. luwenshuni is widely distributed in the small ruminant population in China [19,21,31,41], but its distribution in Thai goats is unknown. The results of the phylogenetic analysis revealed that the T. luwenshuni isolates in this research were closely related to T. luwenshuni isolates from China, suggesting that the parasite may have invaded Thailand through the passage of infected tick vectors or animals from China.…”
Section: Discussionmentioning
confidence: 98%
“…In the neighbouring countries, the prevalence rates of Theileria spp. In goats was 34.7-52.7% from China [19,40,41], 33.3% from Myanmar [24], 8.5% from Bangladesh [42] and 13.4% from Uganda [37].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have highlighted the continued prevalence and impact of this disease on domestic ruminant production, especially compared to cattle. In China, for example, a study by Yang et al . (2022) found that Theileria infections were common among goats, while a recent study by Rahravani et al .…”
Section: Introductionmentioning
confidence: 99%